Exploring three approaches for handling incomplete patient histories in a computer-based guideline for childhood immunization - Miller, P L (Proceedings. AMIA Symposium, 1999)
A significant problem faced by immunization registries is that the dates of a patient's previous vaccinations may not be known. These incomplete histories can pose a problem when attempting to use a computer-based guideline to produce patient-specific immunization recommendations automatically. This paper describes an overall approach, together with 3 specific strategies, developed to help deal with this problem. The paper then describes our experience applying the approach to a database containing over 400,000 immunization histories. The paper also discusses a number of the issues raised in adapting a computer-based guideline to accommodate incomplete patient data of this sort